Perubahan Strategi Petani Dalam Memanfaatkan Lahan Pertanian - Brigita Linda Novrilia; Ridhah Taqwa Ridhah; Rudy Kurniawan Rudy (Master Program in Sociology, Faculty of Social and Political Science, Universitas Sriwijay, 2016)
This thesis entitled